Incomplete vaccination and associated factors among children aged 12-23 months in South Africa: an analysis of the South African demographic and health survey 2016 - Duduzile Ndwandwe; Chukwudi A. Nnaji; Thandiwe Mashunye; Olalekan A. Uthman; Charles S. Wiysonge (Taylor & Francis Group, 2021)
Background Socioeconomic and health inequalities remain a huge problem in post-apartheid South Africa. Despite substantial efforts at ensuring universal access to vaccines, many children remain under-vaccinated in the country. This study aimed to assess the prevalence and factors associated with incomplete vaccination in the first year of life, among children aged 12-23 months in South Africa. Methods The study is a secondary analysis of the 2016 South African Demographic and Health Survey. A multivariable logistic regression model was applied to the data on 708 children aged 12-23 months. The study outcome, vaccination completeness, was assessed using a composite assessment of nine doses of four vaccines; Bacillus Calmette-Guérin (BCG) (one dose), Polio (four doses), diphtheria-tetanus-pertussis containing vaccines (DTP) (three doses) and measles-containing vaccines (MCV) (one dose). Children who received all the nine doses were categorized as completely vaccinated. Independent variables included child, maternal, and demographic characteristics. Variables were included in the model based on literature findings. Bivariate analyses were used to examine the crude association between each independent variable and incomplete vaccination, while the multivariable logistic regression model was used to examine the adjusted association after controlling for other variables. Measures of association were presented as odds ratios (OR) with their 95% confidence intervals (CI). Results About two-fifths (40.8%) of the children were incompletely vaccinated. The prevalence of incomplete vaccination was significantly high among children whose mothers did not receive antenatal care (ANC) during pregnancy (57.5%), and children living in Gauteng Province (52.2%). From the bivariate analyses, the odds of being incompletely vaccinated were three times higher in children whose mothers did not attend ANC compared with children whose mothers attended ANC (crude OR = 2.93; 95% CI 1.42-6.03). The odds were about three times higher in children living in Mpumalanga province (OR = 2.58; 95% CI 1.27-5.25) and in those living in Gauteng province (OR = 2.76; 95% CI 1.30-5.91), compared with those living in Free State province. Conversely, the odds were 32% lower in children from rich households, compared with those from poor households (OR = 0.68; 95% CI 0.47-0.98). In the adjusted model, the higher odds of incomplete vaccination in children whose mothers did not attend ANC were maintained in both magnitude and direction (adjusted OR [aOR] = 2.87; 95% CI 1.31-6.25). Similarly, compared with children living in Free State province, the higher odds of a child being incompletely vaccinated in Mpumalanga (aOR = 2.30; 95% CI 1.03-5.14) and in Gauteng (aOR = 3.10; 95% CI 1.35-7.15) provinces were maintained in both magnitude and direction. Conclusions There is a substantial burden of incomplete childhood vaccination in South Africa. Maternal ANC attendance during pregnancy and area of residence significantly influences this burden. Interventions that promote broader health service utilization, such as ANC attendance, can help improve the awareness and uptake of routine childhood vaccination. It is also imperative to take into consideration the provincial disparities in childhood vaccination completeness, in planning and implementing interventions to improve vaccination coverage in the country.